Understanding the basics of digital business transformation: A Minimal Viable Transformation (MVT) architecture and evidence from firms and women-led MSMEs in India - Bansal, Rohit (Central Community Development Journal, 2024)
This study develops and tests a Minimal Viable Transformation (MVT) architecture, five tightly coupled basics (strategy & culture; staff & customer engagement; process & innovation; digital technology; data & analytics) with an explicit inclusion spine, to convert “digital talk” into measurable performance. Using a multiphase mixed-methods design, we first translate each basic into observable indicators through 28 interviews and two design workshops across sectors and women-led MSMEs. We then validate the measurement model in a cross-sectional survey of 62 organizations (381 multi-role responses) linked, where permitted, to unit-level telemetry and financial/operational data. Finally, we run stepped-wedge field rollouts of 90-day improvement bundles to estimate causal effects. The measurement model supports a higher-order MVT construct. A one-SD increase in MVT is associated with higher customer trust/experience and operational performance, and, where financials are available, meaningful growth/margin uplift. Data & Analytics and Process & Innovation show the strongest direct links to operations, while Strategy & Culture and Staff & Customer Engagement are stronger predictors of trust/experience. Dynamic capabilities and data-driven decisioning partially mediate these effects; inclusion significantly amplifies them. In causal tests, a data-analytics bundle increases conversion and cuts release lead times within one quarter; a customer-journey bundle raises CSAT and reduces churn, effects that are 30–40% larger when paired with concrete inclusion actions. Among 142 home-based women entrepreneurs, lightweight versions of the basics (mobile storefronts, simple OKRs, basic SKU analytics) explain variance in revenue and repeat purchase. The results position MVT as a practical blueprint for firms and MSMEs to prioritize, instruments, and govern transformation, with ecosystem complements (incubators, mentoring) accelerating capability formation.